PROGRESS AND CHALLENGES IN REDUCING WASTE IN THE ENVIRONMENT (TRAKIA JOURNAL OF SCIENCES, 2025)
This study examines the development of mechanisms aimed at achieving the objectives of the circular economy and addressing contemporary environmental challenges. Particular emphasis is placed on enhancing resource efficiency through the reduction of environmental waste. The research identifies key challenges to waste reduction at both macro and micro levels. The study further aims to analyze shifts in individual environmental behavior, using case examples from one of the main districts of the Bulgarian capital, Sofia. The results of the study provide guidelines for managing sustainable consumer behavior.